2013
DOI: 10.1155/2013/380797
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Preoperative Serum CA19‐9 Levels in Patients with Hepatocellular Carcinoma Is Associated with Poor Prognosis after Resection

Abstract: Serum levels of the tumor marker CA19-9 have been reported to be elevated in patients with hepatocellular carcinoma (HCC), but its clinicopathologic significance is still unknown. A cohort of 304 patients undergoing surgical resection for HCC and having preoperative CA19-9 data was enrolled in this study. Serum CA19-9 levels were correlated with clinicopathologic factors. Univariate and multivariate analyses were performed to determine the predictors of patient survival. On receiver operating characteristic cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…Moreover, persistently elevated CA19-9 levels had a strong predictive value for a poor prognosis of hepatobiliary malignancy 25–28. Our current data also supported the predictive value of CA19-9 in hepatic carcinoma patients.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, persistently elevated CA19-9 levels had a strong predictive value for a poor prognosis of hepatobiliary malignancy 25–28. Our current data also supported the predictive value of CA19-9 in hepatic carcinoma patients.…”
Section: Discussionsupporting
confidence: 86%
“…Persistently elevated CA19-9 levels had been reported to predict poor prognosis in HCC. Chen et al [9] found that 34.9% (106/304) of patients with HBV-and HCV-related HCC have CA19-9 levels > 27 U/ml.…”
Section: Discussionmentioning
confidence: 99%
“…It is also frequently elevated in patients with combined HCC-cholangiocarcinoma. Elevated preoperative serum CA19-9 levels have been reported to be associated with worse survival in HCC patients who had undergone resection (> 27 U/mL) or liver transplantation (> 100 U/ml) [8][9][10]. However, most of these studies mainly included patients with HCVrelated HCC who underwent resection or transplantation, and the underlying mechanism by which CA19-9 in uences prognosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…(25) Chen YL et al studied and found that in the 106 hepatocellular carcinoma patients with preoperative CA19-9 levels were >27 U/mL. (26) 4(57.1%) cases of Gastric ca. CA 19-9 levels <35 U/ml and 3(42.9%) cases of Gastric ca.…”
Section: Discussionmentioning
confidence: 99%